2021
DOI: 10.3233/wor-210479
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing job satisfaction among dentists during the new normal of the COVID-19 pandemic in Indonesia: A structural equation modeling approach

Abstract: BACKGROUND: Dentistry is one of the highest risk occupations that face COVID-19, especially in countries that are severely affected by the pandemic, such as Indonesia. OBJECTIVE: The purpose of the study was to determine factors influencing job satisfaction among dentists during the new normal of COVID-19 pandemic in Indonesia by utilizing the Structural Equation Modeling (SEM) approach. METHODS: A total of 310 Indonesian dentists voluntary completed an online questionnaire, which contained 58 questions. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
1
3
1
1
Order By: Relevance
“…Greek dentists seemed to suffer from exhaustion due to COVID-19, with high EE being the most common finding, while other high dimensions of burnout-DP and PA additionally occurred frequently as is also discussed in numerous relevant studies across the globe, before [ 5 , 7 ] and during COVID-19 pandemic [ 14 , 28 , 44 , 45 , 46 , 47 ]. However, this phenomenon was reported in our study at a lower level than elsewhere [ 34 , 35 , 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 88%
“…Greek dentists seemed to suffer from exhaustion due to COVID-19, with high EE being the most common finding, while other high dimensions of burnout-DP and PA additionally occurred frequently as is also discussed in numerous relevant studies across the globe, before [ 5 , 7 ] and during COVID-19 pandemic [ 14 , 28 , 44 , 45 , 46 , 47 ]. However, this phenomenon was reported in our study at a lower level than elsewhere [ 34 , 35 , 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 88%
“…Some participant's expressed that COVID has reduced their workload which allowed for some feeling of satisfaction. Similar findings were made by Prasetyo et al [31] where Indonesian DHPs were found to have significant association with job stress reduction leading to a higher satisfaction level. However, Celik et al [32] concluded that DHPs in the public sector examined reduced number of patients as compared to private practitioners during the pandemic.…”
Section: Discussionsupporting
confidence: 88%
“…Among 24 Indonesian health professionals died from COVID-19, 25% were dentists ( 40 , 41 ). Both Vietnam and Indonesia reported a shortage of PPE as a major hindrance in realizing personnel safety during COVID-19 pandemic ( 39 , 42 ). In Cambodia and the Philippines, Ministry of Health and professional association played an important role in guideline dissemination and ensure the compliance of dental facilities, respectively ( 43 45 ).…”
Section: Discussionmentioning
confidence: 99%